Pemberdayaan Masyarakat Desa melalui Budidaya dan Pengolahan Toga sebagai Alternatif Obat Herbal Keluarga - Desy Fadilah Adina Putri; Hamidatun Rabayya Yusuf; Wa Ode Nanang Trisna Dewi (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Utilization of Family Medicinal Plants (TOGA) is a strategy that is in line with the concept back to nature and family health independence. Rural communities' dependence on synthetic chemical drugs often faces obstacles such as limited access, high costs, and potential side effects, even though Indonesia is rich in medicinal plant biodiversity that has not been optimally utilized. This Community Service (PkM) activity aims to improve the health and economic independence of residents of Pungkit Village, Lopok District, through the optimization of TOGA. The implementation method is based on structured empowerment that includes four main stages: socialization of the importance of "living pharmacies", training in adaptive organic cultivation techniques (using pots, polybags, and vertical culture), education on pre-harvest and post-harvest processing based on hygienic science (such as making dried simplicia, tea bags, and instant powder), and program evaluation. This activity was attended by 45 participants consisting of Posyandu cadres, health cadres, and representatives of heads of families. The results of the activity showed a significant increase in participants' understanding and skills, as seen from the increase in the average evaluation score from 28.75% inpre-testto 86.75% at post-test(increased by 58%). Utilizing yards as TOGA gardens has been proven to support the concept of safe and affordable self-medication, strengthen community social interactions, and open up creative economic opportunities for housewives through local and online marketing of herbal products. The sustainability of this program relies heavily on the commitment of local cadre groups and regular mentoring from academics, village governments, and local community health centers.